The undergraduates’ perspective on shariah audit in islamic banks : An insight to the future shariah auditor labour market in Malaysia / Nor Aishah Mohd Ali and Zurina Shafii - Mohd Ali, Nor Aishah; Shafii, Zurina (Universiti Teknologi MARA Cawangan Pahang, 2014)
Despite the importance of shariah audit, there is little understanding on how to implement an effective and efficient shariah audit from the human capital perspective, particularly in terms of shariah audit education. This study purports to explore the perception of the undergraduates on shariah audit in the Islamic Banks in Malaysia using questionnaire survey in Malaysia. Findings of the paper suggest that there is significant difference between students who are exposed to shariah audit course and those who are not. The study is expected to contribute to the body of knowledge as there is a dearth of Islamic literature on shariah audit education.